Pengaruh metode pembelajaran diskusi terhadap hasil belajar siswa pada mata pelajaran Pendidikan Agama Islam - Pratiwi, Restu Ayu; Ikhtiono, Gunawan; Fadil, Khaidir (Jurnal Pendidik Indonesia, 2024)
This study aims to evaluate the effect of the discussion-based learning method on student achievement in Islamic Religious Education (PAI) at SMA Bosowa. The research uses a quantitative approach with a quasi-experimental design, involving all eleventh-grade students for the 2023-2024 academic year. Purposive Sampling was employed to select the sample, which consisted of experimental and control classes. Data were collected through tests, observation, and documentation, and then analyzed using normality tests, homogeneity tests, and t-tests. The results indicate that the discussion method has a significant impact on students' learning outcomes, as evidenced by the t-test results. This is also reflected in the increase in the average pretest score from 69.55 to 81.88 in the posttest, with a difference of 12.33 points. In conclusion, the use of discussion as an interactive and engaging learning approach has proven effective in enhancing students' understanding of Islamic concepts and their relevance to everyday life.